SQSTM1/p62 Promotes Cell Growth and Triggers Autophagy in Papillary Thyroid Cancer by Regulating the AKT/AMPK/mTOR Signaling Pathway - Yu, Fangqin; Ma, Runsheng; Liu, Chenguang; Zhang, Lele; Feng, Kaixiang; Wang, Meiqi; Yin, Detao (Frontiers in Oncology, 2021)
Background: Thyroid cancer is one of the most common endocrine malignancies worldwide, and papillary thyroid cancer (PTC) is the most common pathologic type of thyroid cancer. SQSTM1/p62 activity mediates different biological functions. This study aimed to investigate the effect of SQSTM1/p62, a multifunctional receptor, on biological function and autophagy characteristics in the human PTC cell line TPC-1. Methods: A total of 105 primary PTC samples and matched adjacent normal thyroid tissue samples were obtained to evaluate the expression of p62 in clinical patients. A similar p62 expression pattern was found in PTC cell lines and normal human thyroid follicular epithelial cells. To evaluate the effect of SQSTM1/p62 on TPC-1 cells, we constructed the p62 knockout cell line p62-KO-TPC-1. Cell proliferation, cell cycle, and cell apoptosis were analysed by colony formation tests, Cell Counting Kit-8 (CCK-8) assays and flow cytometry in vitro. TPC-1 and p62-KO-TPC-1 human PTC cell lines in the logarithmic growth phase were subcutaneously implanted into BALB/c nude mice to verify their proliferation effect in vivo. Furthermore, western blotting and immunohistochemistry (IHC) were used to detect the expression of AKT/AMPK/mTOR signalling pathway-related proteins. Results: Overall, p62 expression was higher in tumour tissues than in normal tissues in 73 of 105 PTC patients (69.5%). The expression level of p62 in the PTC cell line was higher than that in the normal thyroid cell line. Our data indicated that in vitro, p62 deficiency could decrease the number of colonies, inhibit cell growth and the cell cycle, and induce apoptosis. Tumour xenograft experiments in BALB/c nude mice corroborated these findings. Moreover, the molecular mechanism was explored by western blotting, and we found that the AMPK/AKT/ERK pathway was involved. Conclusions: The results indicate that p62 might mediate cell autophagy and apoptosis in TPC-1 cells via the AMPK/AKT/ERK pathway and could be used as a potential therapeutic approach for PTC.